Role of probiotics in oro-dental health - Shiva Mortazavi; Najme Akhlaghi (Isfahan University of Medical Sciences, 2011)
Probiotics are viable microorganisms which improve human health by inhibiting or reducing the number of pathogenic microorganisms. The most common probiotic strains are Lactobacilli and Bifidobacterium. Varying results have been reported about the effect of different probiotic bacterial strains on oral health and decrease in the counts of salivary Streptococcus mutans strains in previous studies. To have a favorable effect on oral health, a probiotic must have the capacity to adhere to tooth surfaces and must be integrated in the bacterial biofilm; it should also be able to compete with cariogenic bacteria and prevent their proliferation. Permanent and daily consumption of probiotics has been recommended for optimal results. Studies have suggested that probiotics can improve the oral cavity microbial equilibrium and the probable benefits increase with an early childhood use; however, caution should be exercised in the administration of probiotics in children because their oral microflora is not been established yet. Although bacteriotherapy with probiotics seems to have inhibitory effects on pathogenic oral microorganisms, further studies are necessary before any recommendations on their clinical use. The aim of this study was to review probiotics, mechanisms of their function, therapeutic effects, application techniques, their cariostatic effects and a review of randomized controlled clinical trials in this regard.Key words: Bifidobacterium, Dairy products, Dental caries, Lactobacilli, Prevention, Probiotics, Streptococcus mutans.